Photodynamic Therapy for Superficial Esophageal Cancer Using an Excimer Dye Laser. Issue 2 (1994) - Mimura, Seishiro; Otani, Toru; Okuda, Shigeru
Abstract : In order to improve the therapeutic effectiveness of photodynamic therapy with Photofrin II and laser light for superficial esophageal cancer, we employed an excimer dye laser instead of an argon dye laser. Eight superficial esophageal cancer lesions (7 cases) were treated. Of these 8 lesions, 6 were cured by initial treatment, while one lesion required another treatment. The final rate of cure was 88% (7/8).